Sistem Charger Station Handphone Dilengkapi dengan Fitur Monitoring dan Radio Frequency Identification - Nadia Ulfa; Muhammad Rusardi; Hilmayuda; Jamilah; Sinek Mehuli Br Perangin-Angin; Asprina Br Surbakti (JURNAL INFORMATIKA DAN PERANCANGAN SISTEM (JIPS), 2023)
Safety in charging cellphone batteries in public places is the most important thing. Places for charging cellphone batteries / Charger stations in public places do not have a good security system so that there are many cases of cellphone theft and so on. A charger station is very important to have security features to avoid these unwanted things. Therefore the use of the RFID (Radio frequency identification) feature is the right thing to make a security system at the charger station. This charger station system uses an Atmega 328 microcontroller to process data and control RFID, LED, and other components.